Qualification Mismatch and Labor Wage Implications - Rahmawati Setiyaningsih; Jihad Panjawa; Lorentino Togar Laut; Rr. Retno Sugiharti (Universitas Negeri Semarang, 2024)
Qualification mismatch is a significant issue in DKI Jakarta’s labor market, affecting how wages are distributed among workers. Although DKI Jakarta has the highest Provincial Minimum Wage (UMP) in Indonesia, many employees still receive wages inconsistent with their educational qualifications in terms of level and field of study. This study employs a quantitative regression approach using data from SAKERNAS August 2023 DKI Jakarta to analyze the impact of educational mismatch on labor wages. The results highlight a widespread issue of undereducation, where workers earn less than expected based on their qualifications. On the other hand, overeducation and mismatches in education do not significantly influence wage levels. Key factors such as education level, squared experience, undereducation, and gender have a significant positive effect on wages while working hours exert a significant negative impact. Interestingly, variables like technology use, internet access, and training opportunities show no substantial effect on wage determination. The study suggests that policymakers must address these mismatches by promoting gender equality and enhancing information and communication technology to improve productivity and wage outcomes across the labor force in DKI Jakarta